2023
DOI: 10.1371/journal.pone.0282789
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital stress and patient outcomes: A systematic review and meta-analysis

Abstract: Background Hospital inpatients are exposed to high levels of stress during hospitalisation that may increase susceptibility to major adverse health events post-hospitalisation (known as post-hospital syndrome). However, the existing evidence base has not been reviewed and the magnitude of this relationship remains unknown. Therefore, the aim of the current systematic review and meta-analysis was to: 1) synthesise existing evidence and to determine the strength of the relationship between in-hospital stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The practice of PMR and similar techniques can lead to improved concentration, decision-making, and emotional resilience for medical professionals. This, in turn, has the potential to enhance patient interactions and outcomes, as healthcare providers who are mentally stable and less stressed are more likely to be attentive and empathetic in their patient care (Ford et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The practice of PMR and similar techniques can lead to improved concentration, decision-making, and emotional resilience for medical professionals. This, in turn, has the potential to enhance patient interactions and outcomes, as healthcare providers who are mentally stable and less stressed are more likely to be attentive and empathetic in their patient care (Ford et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, multivariable MR Models were constructed to analyze the direct or independent effects of Hba1c, T1DM, and other characteristics on outcomes. The model was developed to determine the major factors affecting the prognosis of vitiligo, At present, some studies(911) have suggested that glycosylated hemoglobin has statistical significance in peripheral blood of vitiligo patients, and glycosylated hemoglobin is one of the indicators of type 1 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Pagyvenę žmonės, patekę į gydymo institucijas, taip pat patiria didelį stresą, dėl kurio gali padidėti polinkis į nepageidaujamus sveikatos reiškinius po hospitalizacijos (vadinamasis posthospitalinis sindromas). Daroma prielaida, kad psichologinis stresas, kurį patiria stacionare gydomi pagyvenę žmonės, yra susijęs su prastesniais jų gydymo rezultatais [5].…”
Section: Tyrimo Rezultataiunclassified